Promoting mental health in esports - Kegelaers, Jolan; Trotter, Michael G.; Watson, Matthew; Pedraza-Ramirez, Ismael; Bonilla, Iván; Wylleman, Paul; Mairesse, Olivier; Van Heel, Martijn (Frontiers in Psychology, 2024)
There is growing recognition of the demands and health challenges experienced by esports athletes. The purpose of this perspective paper is to draw specific attention to the mental health of competitive gamers and spur on both future research and applied initiatives focussing on this important but under-addressed topic. We will briefly discuss the prevalence of mental health concerns, domain-specific stressors, and the need for comprehensive mental health support systems tailored to the esports context. It is our hope that, with this perspective paper, we can help set a new research agenda addressing mental health in esports.